Medium-term cost-effectiveness of an automated non-invasive ventilation outpatient set-up versus a standard fixed level non-invasive ventilation inpatient set-up in obese patients with chronic respiratory failure: a protocol description. Issue 4 (23rd April 2015) - Mandal, S; Arbane, G; Murphy, P; Elliott, M W; Janssens, J P; Pepin, J L; Muir, J F; Cuvelier, A; Polkey, M; Parkin, D; Douiri, A; Hart, N
Abstract : Introduction: Obesity is an escalating issue, with an accompanying increase in referrals of patients with obesity-related respiratory failure. Currently, these patients are electively admitted to hospital for initiation of non-invasive ventilation (NIV), but it is unknown whether outpatient initiation is as effective as inpatient set-up. We hypothesise that outpatient set-up using an autotitrating NIV device will be more cost-effective than a nurse-led inpatient titration and set-up. Methods and analysis: We will undertake a multinational, multicentre randomised controlled trial. Participants will be randomised to receive the usual inpatient set-up, which will include nurse-led initiation of NIV or outpatient set-up with an automated NIV device. They will be stratified according to the trial site, gender and previous use of NIV or continuous positive airway pressure. Assuming a 10% dropout rate, a total sample of 82 patients will be required. Cost-effectiveness will be evaluated using standard treatment costs and health service utilisation as well as health-related quality of life measures (severe respiratory insufficiency (SRI) and EuroQol-5 dimensions (EQ-5D)). A change in the SRI questionnaire will be based on the analysis of covariance adjusting for the baseline measurements between the two arms of patients. Ethics and dissemination: This study has been approved by the Westminster National Research Ethics Committee (11/LO/0414) and is the trial registered on the UKCRN portfolio. The trial is planned to start in January 2015 with publication of the trial results in 2017. Trial registration number: ISRCTN 51420481.